Primary ovarian insufficiency quality of life scale (POIQOLS): development and psychometric properties - Samira Golezar; Zohreh Keshavarz; Fahimeh Ramezani Tehrani; Abbas Ebadi; Farid Zayeri; Mohammad Hossein Golezar (BMC, 2022)
Abstract Background Primary ovarian insufficiency is menopause before the age of 40. It can affect the quality of life of afflicted women. Because there is no instrument available for measuring the quality of life of these women, the present study was carried out to develop and assess the psychometric properties of the quality of life scale for women with primary ovarian insufficiency. Methods This exploratory sequential mixed method study was performed in two phases. In the qualitative phase (item generation), semi-structured in-depth interviews were conducted with 16 women having primary ovarian insufficiency, and a literature review was performed to generate initial items pool. In the quantitative phase (psychometric evaluation), the face, content, and construct validity (exploratory factor analysis), as well as reliability (internal consistency and test-retest methods), were evaluated. Besides, the responsiveness and interpretability were investigated. Results During the first phase of the study, the initial item pool was generated with 132 items. After the face and content validity, the number of items was reduced to 40. The results of exploratory factor analysis yielded a 28 item scale with six factors. These factors explained 58.55% of the total variance. The Cronbach's alpha for each factor was more than 0.7. Furthermore, the intraclass correlation coefficient for the entire scale was 0.95. Conclusions The primary ovarian insufficiency quality of life scale (POIQOLS) is a valid and reliable tool for accessing the quality of life of women with primary ovarian insufficiency.